Peran Perguruan Tinggi dalam Pemberdayaan Masyarakat Melalui Bank Mikro Waka - Rimanto Rimanto; Kholid Hidayatullah; Muhamad Rudi Wijaya (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Waqf plays a very significant economic and social position in Islamic history. Waqf acts as a source of financing for worship, education, social and public services. Many developments in the Islamic economic sector or Islamic banking are related to waqf, not least in 2017 the Government together with the OJK initiated the existence of a Micro Waqf Bank as an effort to answer the problem of poverty, in collaboration with Islamic boarding schools in Indonesia. using primary and secondary data using descriptive qualitative analysis. The results of this research prove that the term Micro Waqf Bank was chosen because the government wants the core of the funds distributed to the community to be maintained in principle without reducing the benefits, not only that it is called Micro Waqf Bank because the BWM operation is located in a boarding school area. Throughout the development of this BWM, using the term micro waqf bank in naming the institution, but from the legal basis and the form of the legal entity it is very far from the name. The legal entity of BWM is a cooperative, on the other hand, the business license of BWM is a sharia microfinance agency, so its supervision is under the Financial Services Authority. The involvement of Universities in the context of community service for community empowerment is very strategic in order to carry out complete human development, and in the context of community empowerment and Micro Waqf Bank instruments have the potential for community economic development, especially in the pesantren environment, to create an empowered, independent and independent society